Analysis of Genetic Variations in PHT1 Gene Sequences in Rice (Oryza sativa) NCBI Popset 240028097 Using In-Silico RFLP - Oliv Nurul Kanaya Nurul Kanaya; Afifatul Achyar (Jurnal Serambi Biologi, 2023)
Abstract Rice is a plant that has high economic value. According to FAO, Indonesia is the third largest rice consuming country in the world. However, rice will become stunted and its growth will be stunted if there is a lack of phosphorus. The PHT1 gene plays an important role in plant growth and development, because this gene plays a role in taking phosphate from the soil. The PHT1 gene is transcribed when there is drought, salt stress, and nutrition in plants. Genetic variation in a population will affect the survival of an individual. This study used the restriction enzyme ScaI. This study aims to analyze genetic variation in the PHT1 gene sequence in NCBI Popset 2400280979 rice using RFLP in silico. The results showed that there was genetic variation in the rice PHT1 gene sequence and two allele variations present in 24 rice gene sequences using the restriction enzyme ScaI.